Risk factor analysis of Campylobacter spp., Listeria monocytogenes and Salmonella spp. in the chicken meat value chain - Sneha, E.N.P.; Sanjumon, E.S.; Hung Nguyen-Viet; Dubal, Z.B.; Bhilegaonkar, K.N.; Ayoub, H.; Grace, Delia; Akash, B.; Gangwar, A.; Manoj, S.; Premkumar, D.; Dhanze, H.; et al. (Frontiers Media, 2026)
Introduction: A cross-sectional study was conducted to evaluate microbiological risk factors associated with Salmonella spp., Campylobacter spp., and Listeria monocytogenes along the chicken meat value chain in Bareilly district, Uttar Pradesh, India.